Green Energy for Belt and Road Initiative: Economic Aspects Today and in the Future - Chernysheva, Natalia A.; Perskaya, Victoria V.; Petrov, Alexander M.; Bakulina, Anna A. (International Journal of Energy Economics and Policy, 2019)
The Belt and Road Initiative (BRI) is a comprehensive megaproject, which includes numerous projects in the sphere of green energy. The effectiveness of these projects is often doubted. The article reveals the main mechanisms of green energy projects' influence on the economy and through the research of 8 BRI countries demonstrates the method of green energy projects efficiency estimation. China is considered to be the main driver for green energy proliferation in Asia, receiving economic benefits through its policy. The authors prove this to be right, but the effects for PRC differ in short and long-run periods. The main findings of the paper are that the BRI green energy dissemination is just the first step to building a tightly interconnected Asian energy infrastructure, and that the BRI least developed countries have less positive long-run effects from green energy investment, while in short-term they get a boost for their economies. Keywords: BRI, green energy, energy, Asian region, China, JEL Classifications: F21; K32; O44 DOI: https://doi.org/10.32479/ijeep.8045